การจัดการความรู้เพื่อการสืบทอดวัฒนธรรมการใช้เรือพื้นบ้านไทยภาคกลาง (KNOWLEDGE MANAGEMENT FOR CONTINUITY OF NATIVE BOAT CULTURE CENTRAL THAILAND) - เหมือนวิหาร จิรัฏฐ์ (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2015)
บทคัดย่อ วัตถุประสงค์หลักของเรื่องการจัดการความรู้เพื่อการสืบทอดวัฒนธรรมการใช้เรือพื้นบ้านไทยภาคกลาง คือการนำบทบาทของการจัดการความรู้ ในการฟื้นฟูวัฒนธรรมการใช้เรือพื้นบ้าน ซึ่งอยู่ในกระบวนการที่สูญหายไป เป็นการวิจัยในเชิงคุณภาพเป็นหลัก (Qualitative research) โดยการสัมภาษณ์และมีการผสมผสานรูปแบบของการวิจัยเชิงเอกสาร (Documentary research) วิจัยเชิงประวัติศาสตร์ (Historical research) ผลการวิจัย พบว่า 1) กระบวนการแสวงหาความรู้มีผลต่อการสืบทอดวัฒนธรรมการใช้เรือพื้นบ้าน 2) สังคมวัฒนธรรมการใช้เรือพื้นบ้านมีผลต่อการสืบทอดวัฒนธรรมการใช้เรือพื้นบ้าน 3) การเผยแพร่ความรู้มีผลต่อการสืบทอดวัฒนธรรมการใช้เรือพื้นบ้าน 4) การใช้ความรู้เรื่องเรือพื้นบ้านมีผลการสืบทอดวัฒนธรรมการใช้เรือพื้นบ้าน และยังมีสังคมที่ใช้เรือพื้นบ้านอยู่จริงในปัจจุบัน ผู้วิจัยมีข้อเสนอแนะ 1) กระบวนการการจัดการความรู้ควรมี 6 ขั้นตอน คือ การแสวงหาความรู้ การสร้างความรู้ การเผยแพร่ความรู้ การใช้ความรู้ การเก็บรักษาความรู้ และการประเมินผลความรู้ 2) ควรมีการส่งเสริมการท่องเที่ยวในภูมิภาคไทยภาคกลางโดยนำเรือพื้นบ้านมาใช้เพื่อสืบทอดวัฒนธรรมอย่างต่อเนื่องและยั่งยืน Abstract The main objective of the thesis entitled, Knowledge Management for Continuity of Native Boat Culture in Central Thailand, is to investigate the roles played by knowledge management to revive Thai native boat culture which is in the process of declining in central Thailand using qualitative research method broadly and historical study in specific. The research findings confirms the working hypotheses that: 1) There exist native boat building in the region. 2) There exist native boat using society and culture in the region. 3) The distribution of knowledge management processes in reviving the boat utilization culture. 4) There exist at the juncture the actual utilization of boat culture in the region. The thesis then ended with many interesting recommendations as to how to make best uses of the research findings. It is suggested that: 1) the process of knowledge management should contain of 6 steps : searching, creation, distribution, knowledge usage, conservation, and evaluating knowledge illustrated by a model. 2) to assist the knowledge management process in the continuation of native boat culture, it is recommended to promote tourist activities utilizing native boats.